2007
DOI: 10.1063/1.2802300
|View full text |Cite
|
Sign up to set email alerts
|

Effects of topology and size on statics and dynamics of complexes of hyperbranched polymers with linear polyelectrolytes

Abstract: Brownian dynamics simulations with explicit hydrodynamic interactions have been employed to study generic effects of size and topology in noncovalent ͑Coulombic-driven͒ complexes formed by irregular-shaped hyperbranched polymers and linear polyelectrolytes. The behavior of the complexes was explored in detail in terms of static and dynamic properties, both in local and in the entire complex scale. The results were compared to previous studies on perfect dendrimers and other hyperbranched molecules where availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 31 publications
4
41
0
1
Order By: Relevance
“…The HP constituents bear different sizes and extremely different branching structures allowing the assessment of the effects of molecular weight and topology on their response under shear flow. As it was demonstrated in our previous work where their equilibrium properties were examined, 34,38 complexes formed by HPs that are characterized by a dense branching pattern throughout the structure exhibit properties similar to those of systems formed by perfect dendritic analogs; this similarity allows them to be considered as cost-effective alternatives in relevant applications. On the other hand, complexes formed by the more open-in-structure, peripherally branched HPs exhibited remarkable differences from the former, both in static and in dynamic properties.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The HP constituents bear different sizes and extremely different branching structures allowing the assessment of the effects of molecular weight and topology on their response under shear flow. As it was demonstrated in our previous work where their equilibrium properties were examined, 34,38 complexes formed by HPs that are characterized by a dense branching pattern throughout the structure exhibit properties similar to those of systems formed by perfect dendritic analogs; this similarity allows them to be considered as cost-effective alternatives in relevant applications. On the other hand, complexes formed by the more open-in-structure, peripherally branched HPs exhibited remarkable differences from the former, both in static and in dynamic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Differences, however, have been detected when the HP constituent was characterized by a more "open" structure bearing the dendritic branching units close to the periphery. 34,38 For all complexes, however, it was found that either in terms of conformational characteristics or in terms of global dynamics, the behavior of the linear chains was altered compared to their neutral counterparts, particularly when the size of the HP molecule was increased.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations